SOSIALISASI PEMBUATAN BETON HIGH EARLY STRENGTH MENGGUNAKAN SUPERPLASTICIZER, ACCELERATOR, SILICA FUME DAN SERAT POLYPROPYLENE - Lina Flaviana Tilik; Bastoni Bastoni; Muhammad Sazili Harnawansya (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Infrastructure development in the construction sector still largely uses conventional methods, which result in delays in construction time and high maintenance costs, particularly due to the lengthy concrete hardening process. Local construction workers' lack of understanding of modern additive-based High Early Strength concrete technology is one of the main causes of these problems. This community service activity aims to provide socialization and transfer of High Early Strength concrete production technology by utilizing a combination of superplasticizer, accelerator, silica fume, and polypropylene fiber additives to PT. Pratista Shaqu Unggul's partners. The activity was carried out through the stages of problem identification, socialization, concrete mixing simulation, interactive discussions, and the development of practical technical guidelines. The activity results showed that 85% of participants understood the function of additives and showed a high interest in adopting this technology in their work. The application of the High Early Strength concrete formulation has been proven to overcome the problem of concrete hardening time and increase the efficiency of project implementation. This activity has succeeded in increasing the knowledge and technical skills of partners, encouraging changes in work patterns towards more efficient modern construction, and opening opportunities for independent application of this technology in the small and medium construction sector.